Creep and relaxation responses of fly ash concrete: Linear and nonlinear cases. (December 2022) - Qu, Zhiwei; Si, Ruizhe; Jia, Pengjiao; Zhang, Yingda
Abstract: The application of reinforced concrete has been used in various engineering and architecture fields. Stress relaxation and creep are two crucial time-dependent behaviours of concrete. The influence of two behaviours is closely related to the service life of the reinforced concrete structure. However, the research on experimental relaxation behaviour has rarely been extensively studied because of the complicated procedures. Meanwhile, fly ash is commonly utilised to partially replace cement to reduce the greenhouse effect. As a result, this study is committed to examining the creep and relaxation behaviour of fly ash concrete. The concrete creep and relaxation tests were designed to maintain a constant stress and strain levels, respectively. The creep and relaxation tests were conducted at the same time to minimise the shrinkage and ageing effects. The stress and strain levels were selected as 20% and 60% of concrete compressive strength to investigate creep and relaxation in linear and nonlinear cases. By comparing computed values of relaxation from the inverse of the compliance function, the estimated relaxation function showed good agreement using the inverse of the compliance function. However, the existing creep model showed a difference in predicting the creep of fly ash concrete. As a result, the existing model is amended to improve the estimation of creep and relaxation of fly ash concrete.